PERANCANGAN SISTEM INFORMASI PEMESANAN TIKET PESAWAT DOMESTIK BERBASIS WEB PADA CV JENIKA GROUP DEPOK - Guskani, Adelia; Ayu Muthia, Dinda (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
Based on the Tiket.com survey in the third quarter of 2020, there was a three-fold increase in transactions that occurred in hotel booking services and flight bookings. This increase is considered very fast in the midst of the Covid-19 pandemic due to the encouragement of people to take vacations in the midst of the pandemic. To be able to compensate for the increase that occurred, tour and travel companies are required to be able to optimize services by computerizing the flight ticket booking system. Therefore, the author intends to create a website for booking domestic airline tickets for CV JENIKA GROUP Depok. The author uses a method that has proven its effectiveness in designing an information system, namely the Waterfall method. Based on the results of the study, it can be concluded that the design of this web-based domestic flight ticket booking program can provide convenience and comfort for admins and customers of CV JENIKA GROUP and can further expand marketing reach.